Angle-selective surface based on multi-layered frequency-selective surfaces - Hong, Yujing (Nanyang Technological University, 2023)
Angle-selective surfaces (ASSs) can provide angular selectivity for the incident plane electromagnetic waves. One way to realize such angular selectivity is to employ multilayered frequency-selective surfaces (FSSs). By properly designing individual FSS layers, bandpass and band-stop properties can be obtained under normal and oblique incidences, respectively. In this thesis, a concept of 3D angle-selective surfaces is proposed, which introduces a vertical component to the structure and provides an extra degree of freedom for designing. Based on the equivalent circuit method, stacking two layers of 3D ASSs with an air space between them can further improve the sharpness of angular selectivity and achieve a wider bandwidth. A dual-polarized bilayer 3D angle-selective surface with an operating frequency of 10 GHz is presented and simulations are conducted to verify the theoretical design. The simulation results show that a passband with |S21| higher than -1 dB from 0° to 17° and a stopband with |S21| less than -15 dB from 47° to 80° are obtained for TE-polarized incidence while a passband with |S21| higher than -1 dB from 0° to 10° and a stopband with |S21| less than -15 dB from 25° to 80° are obtained for TM-polarized incidence.